Effect of Anaplasma spp. infection on some blood parameters in Awassi local breed sheep - Al-Rubaii, H.M. A.S. (The Iraqi Journal of Veterinary Medicine, 2008)
The aim of this study to investigation the effect of Anaplasma spp.infection on some blood parameters by collecting 65 blood samplesfrom Awassi local breed sheep. The total infection rate 26.15 % whichdivided into 25 % in males and 26.31 % in females. The parasitemiarange between 0.5-4 % (mean 1.97 %).The infected animals showed anemia represented by decrease meansof packed cell volume (P<0.01), red blood cell count (P<0.05) andhaemoglobin concentration, While increase corpuscular volume,corpuscular haemoglobin and corpuscular haemoglobin concentration(P<0.05). As well as decrease total white blood cell count and monocyteswhile increase lymphocytes, neutrophils , eosinophils, basophils andplatelets comparison to non infected animals.Our conclusion refered to the direct effect of Anaplasma parasite onsome blood parameters in the infected Awassi local breed sheep.